Developing Competitiveness and Quality Assurance in Daâ€™wa and Communication Faculty, Islamic State University Ar-Raniry - Hendra Syahputra (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2013)
Competitiveness is one of the goal for the success of an organization, including educational institution. The success of a reliable competitiveness is inseparable from the quality of leadership and the leader who is carrying out the organization. In order to realize an exceptional competitiveness, there should be a strong quality assurance at all organization-line. line. The objective of this paper is to analyze the leadership ethic in an educational institution that is trying to upgrade its status as well as try to provide some solutions regarding competitiveness and leadership. The most needed competitiveness in all quality assurance concepts is having a visionary leader since IAIN is trying to be a UIN. The flexibility of the leader success and respons which are vary have to be a consitency of value and basic rules, if the profesional credibility of a leader is still regarded as a significant source of influence. Credibility, in turn, is more than professional consistency dan compentency in the role of a leader. This is because the leader is the number one hope of the leds, therefore the success of a leader as a manager not only assterted by organization but also acknowledged in the heart of the leds. This endorsement is not only about â€œwhether the leader is trusted but also whether the leader is trusted by the leds.â€